Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Baris Jaya Perkasa - Dinda Auliya Pratiwi; Fauziah Afriyani; Try Wulandari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine and analyze the influence of leadership style and work motivation variables on the performance of PT Baris Jaya Perkasa employees. This shows that the leadership style is sometimes still very weak and still really needs attention to improve employee performance. This research uses a quantitative approach using survey methods and the technique used is a questionnaire. The population or respondents in this research were 52 employees at PT Baris Jaya Perkasa. The results of this research are t count 4.092 > t table 2.010 on the leadership style variable (X1) and t count 7.043 > 2.010 on the work motivation variable (X2). In the correlation coefficient test method for the leadership style variable (X1), the value is 0, which means that the level of relationship between leadership style (X1) and employee performance (Y) is at a low level of relationship. However, in the research, the work motivation variable (X2) has a value of 0.706, which means that the level of relationship between work motivation (X2) and employee performance (Y) is at a strong relationship level. Based on the results of calculating the coefficient of determination (R2), it can be concluded that the percentage influence of the variables leadership style (X1) and work motivation (X2) on employee performance (Y) is 0.519 or 51.9%, the remaining 48.1% is influenced by other variables.